Pengaruh Kepercayaan Merek, Persepsi Kualitas, Dan Harga Terhadap Loyalitas Pelanggan Kosmetik Maybelline (Studi Pada Mahasiswa Aktif Fakultas Ekonomi Dan Bisnis Universitas Wijaya Kusuma Surabaya) - Reza, Charolina Therezia; Indahwati, Indahwati (PRAGMATIS, 2024)
The focus of this research is to assess the effect of brand trust, perceived quality, and price on customer loyalty for Maybelline cosmetic products. The parameters of the independent variables studied are brand trust, perceived quality, and price with the dependent variables being customer loyalty. The population in this study were students of the Faculty of Economics and Business, Wijaya Kusuma University Surabaya. Sample determination using non probability sampling method with purposive sampling technique with criteria 1) Female and an active student of FEB UWKS, 2) Have made a purchase transaction for Maybelline cosmetic products, 3) Use the product personally, 4) Make purchases more than 2 times. The number of samples in this study were 47 respondents. This study uses linier regression analysis as the analysis technique. The research findings reveal that brand trust has a significant influence on customer loyalty. On the other hand, perceived quality does not show a significant effect on customer loyalty and price has a significant effect on customer loyalty. Based on the result of the f test, all independent variables can be used to predict Y.